Neurally Mediated Airway Constriction in Human and Other Species: A Comparative Study Using Precision-Cut Lung Slices (PCLS) - Schlepütz, Marco; Rieg, Annette D.; Seehase, Sophie; Spillner, Jan; Perez-Bouza, Alberto; Braunschweig, Till; Schroeder, Thomas; Bernau, Marc; Lambermont, Verena; Schlumbohm, Christina; Sewald, Katherina; Autschbach, Rüdiger; et al. (PLOS ONE, 2012)
The peripheral airway innervation of the lower respiratory tract of mammals is not completely functionally characterized. Recently, we have shown in rats that precision-cut lung slices (PCLS) respond to electric field stimulation (EFS) and provide a useful model to study neural airway responses in distal airways. Since airway responses are known to exhibit considerable species differences, here we examined the neural responses of PCLS prepared from mice, rats, guinea pigs, sheep, marmosets and humans. Peripheral neurons were activated either by EFS or by capsaicin. Bronchoconstriction in response to identical EFS conditions varied between species in magnitude. Frequency response curves did reveal further species-dependent differences of nerve activation in PCLS. Atropine antagonized the EFS-induced bronchoconstriction in human, guinea pig, sheep, rat and marmoset PCLS, showing cholinergic responses. Capsaicin (10 µM) caused bronchoconstriction in human (4 from 7) and guinea pig lungs only, indicating excitatory non-adrenergic non-cholinergic responses (eNANC). However, this effect was notably smaller in human responder (30±7.1%) than in guinea pig (79±5.1%) PCLS. The transient receptor potential (TRP) channel blockers SKF96365 and ruthenium red antagonized airway contractions after exposure to EFS or capsaicin in guinea pigs. In conclusion, the different species show distinct patterns of nerve-mediated bronchoconstriction. In the most common experimental animals, i.e. in mice and rats, these responses differ considerably from those in humans. On the other hand, guinea pig and marmoset monkey mimic human responses well and may thus serve as clinically relevant models to study neural airway responses.